Pembuatan Film Pendek “Berbagi Asa” Dengan Menggunakan Teknik Color Grading dalam Editing - Muhammad Maulana; Agusdi Syafrizal; Farindika Metandi (JURNAL VOKASI TEKNIK, 2025)
Technological developments in the digital era have made multimedia an important element in conveying information. One effective form of multimedia is short films, audio-visual media that are able to convey messages easily and are interesting to the public. The short film BERBAGI ASA was developed to promote the KIP-Kuliah Program and Samarinda State Polytechnic Campus, a tertiary institution that offers various study programs and educational scholarships. The process of making this film uses the Multimedia Development Life Cycle (MDLC) method, which consists of six stages: Concept, Design, Material Collecting, Assembly, Testing, and Distribution. This method was chosen because of its ability to ensure that each design step is carried out in a structured and efficient manner. Apart from that, color grading techniques are applied at the editing stage to improve visual quality, so that the final result is more attractive and professional. The short film BERBAGI ASA succeeded in meeting the target of 3000 views in three days, produced through this process and used as informative and inspirational promotional media, helping to increase public understanding of the benefits of the KIP-Kuliah Program and introducing the Samarinda State Polytechnic more widely.